2022
DOI: 10.3390/foods11162441
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Botanical Origin of Italian Honey by Carbohydrate Composition and Volatile Organic Compounds (VOCs)

Abstract: Honey is a natural sweetener constituted by numerous macro- and micronutrients. Carbohydrates are the most representative, with glucose and fructose being the most abundant. Minor honey components like volatile organic compounds (VOCs), minerals, vitamins, amino acids are able to confer honey-specific properties and are useful to characterize and differentiate between honey varieties according to the botanical origin. The present work describes the chemical characterization of honeys of different botanical ori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 56 publications
2
11
0
Order By: Relevance
“…Minimum percent of pollen for the characterization of monofloral honey is excepted in Robinia pseudoacacia (Italy-15%; Germany-20%; Croatia-20%; Serbia-20%; Romania-25%), Tilia spp. (Germany-20%; Croatia-25%; Serbia-25%; Romania-30%), and Helianthus annuus (Romania-40%) [3,12]. The differences can be seen in the FTIR spectral analysis, where, after examining sample S1, linden honey (Tillia sp.…”
Section: Physicochemical Determinationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Minimum percent of pollen for the characterization of monofloral honey is excepted in Robinia pseudoacacia (Italy-15%; Germany-20%; Croatia-20%; Serbia-20%; Romania-25%), Tilia spp. (Germany-20%; Croatia-25%; Serbia-25%; Romania-30%), and Helianthus annuus (Romania-40%) [3,12]. The differences can be seen in the FTIR spectral analysis, where, after examining sample S1, linden honey (Tillia sp.…”
Section: Physicochemical Determinationsmentioning
confidence: 99%
“…Honey is heavy, with a mean value of specific gravity of 1.4 g/cm 3 . Specific gravity has a practical significance in keeping track of the amount of honey safely stored because it is correlated with moisture content.…”
Section: Physicochemical Determinationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The slides were then placed on a hot plate for 10 min. After drying, a drop of glycerin gelatin was dropped into it, which was then covered with a cover slip for identification [47].…”
Section: Standard Physicochemical Parameters and Pollen Analysismentioning
confidence: 99%
“…A combination of GC-MS and SPME offers more information, including retention time (R t ), mass fragments for the volatile compounds, and more precise qualitative and quantitative results. The analysis of volatile compounds in foods, including fruits, vegetables, tea, wine, and honey, has been extensively conducted using this technique [47]. In the current study, 37 volatile compounds were identified and grouped into aldehydes (64.67 vs. 32.8%), ketones (16.54 vs. 32.04%), phenols (10.31 vs. 4.45%), acids and esters (7.46 vs. 23.01%), anthraquinone (0 vs. 6.38%), hydrocarbon (0.59 vs. 0%), and nitrogenous compounds (0.37 vs. 1.06%) for honey from Saudi Arabia and Egypt, respectively (Table 3).…”
Section: Gc-ms Analysismentioning
confidence: 99%